Neuroprotective and therapeutic effects of calcitriol in rotenone-induced Parkinson’s disease rat model - Magdy, Alshimaa; Farrag, Eman A. E.; Hamed, Shereen Mohamed; Abdallah, Zienab; El Nashar, Eman Mohamad; Alghamdi, Mansour Abdullah; Ali, Amira A. H.; Abd El-kader, Marwa (Frontiers in Cellular Neuroscience, 2022)
Parkinson's disease (PD) is the second most common neurodegenerative disease. Treatment of PD is challenging, as current treatment strategies are only symptomatic and do not stop disease development. Recent studies reported neuroprotective effects of calcitriol in PD through its antioxidant and anti-inflammatory properties. The exact pathomechanisms of PD are not yet fully understood. So, investigation of different molecular pathways is challenging. Sirtuin-1 (Sirt1) modulates multiple physiological processes, including programmed cell death, DNA repair, and inflammation. Furthermore, defective autophagy is considered a key pathomechanism in PD as it eliminates protein aggregation and dysfunctional cell organelles. The present study investigated the involvement of autophagy and Sirt1/NF-κB molecular pathway in rotenone-induced PD and explored the protective and restorative effects of calcitriol through these mechanisms. Therefore, behavioral tests were used to test the effect of calcitriol on motor disability and equilibrium. Furthermore, the histological and neuronal architecture was assessed. The expression of genes encoding neuroinflammation and autophagy markers was determined by qPCR while their protein levels were determined by Western blot analysis and immunohistochemical staining. Our results indicate that behavioral impairments and dopaminergic neuron depletion in the rotenone-induced PD model were improved by calcitriol administration. Furthermore, calcitriol attenuated rotenone-induced neuroinflammation and autophagy dysfunction in PD rats through up-regulation of Sirt1 and LC3 and down-regulation of P62 and NF-κB expression levels. Thus, calcitriol could induce a neuro-protective and restorative effect in the rotenone-induced PD model by modulating autophagy and Sirt1/NF-κB pathway.